(untitled) (Journal of Computational Mathematics, 2023)
In the existing work, the recovery of strictly k-sparse signals with partial support information was derived in the 2113_2 bounded noise setting. In this paper, the recovery of approximately k-sparse signals with partial support information in two noise settings is investigated via weighted 2113_p (0 < p 2264 1) minimization method. The restricted isometry constant (RIC) condition 03b4_tk